2004
DOI: 10.2139/ssrn.555724
|View full text |Cite
|
Sign up to set email alerts
|

Does Accessibility to Higher Education Matter? Choice Behavior of High School Graduates in the Netherlands

Abstract: This paper identifies pivotal factors behind individual decision making in the transition from high school to post-secondary education in the Netherlands. We apply a multinomial logit framework to individual data and accommodate two types of effects that have not received much attention in the literature. First, we analyse the impact of geographical accessibility of the higher education system. Second, we allow the individual observations to be correlated within schools, in effect accounting for localized soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…They even distinguish between types of institutions. Results indicate that geographical proximity increases the chances of entering education at a university or college (Sa et al 2004;Flannery and Cullinan 2014).…”
Section: Educational Infrastructure and The Transition To Universitymentioning
confidence: 96%
“…They even distinguish between types of institutions. Results indicate that geographical proximity increases the chances of entering education at a university or college (Sa et al 2004;Flannery and Cullinan 2014).…”
Section: Educational Infrastructure and The Transition To Universitymentioning
confidence: 96%
“…In the United States of America, Do (2004) and Griffith and Rothstein (2009) revealed that the opportunity for poorer students to attend governmental universities increases if they live near the university. Similarly, Sa et al (2006) noted that the geographic distance to vocational universities and colleges increases the probability of school graduates continuing their education beyond high school in the Netherlands. Based on their study on students from the United Kingdom, Gibbons and Vignoles (2009) concluded that the distance from their houses to their schools affects the selection of the closest college or university.…”
Section: Introductionmentioning
confidence: 94%
“…Students' family financial capability and educational attainment level may exert great influences upon whether they would choose to study pharmacy (Witteman et al 1975). In general, studies have shown that the higher the household income and the greater the demand for a college education, the more choices that student will have (Sa 2006). It appears that families with higher income are more capable of supporting their children's college education.…”
Section: Choice Of Pharmacy Schoolmentioning
confidence: 99%
“…For example, with the increased distance from home to school, the flow of information about the school declines, the transportation costs increase, the option for other competing schools increases, and the psychic costs also gets higher (Leppel 1993). While distance itself might be used as a single factor, it is also used to measure the accessibility of individual schools (Sa 2006). This approach could be perceived as a variant of the gravity model.…”
Section: Choice Of Pharmacy Schoolmentioning
confidence: 99%
See 1 more Smart Citation